TEACHERS’ PERSPECTIVES ON CHARACTERISTICS OF GOOD LANGUAGE LEARNERS - Yayu Sri Rahayu; Muhamad Taufik Hidayat; Amir Hamzah (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The study aim to obtain insight into teachers’ perspectives on characteristics of a good language learners. To fulfill this aim, qualitative method was employed in this study. The study applied a case study research design. The study was conducted in one of a universities in Garut, West Java. The researcher interviewed three lectures in the English education program. The data were collected from materials, tools for recording, participants as the object of the study, and transcription. The data were then analyzed inductive analysis which concerned with the generation of new theory emerging from the data. The inductive approach is a systematic procedure for analyzing qualitative data where the analysis is guided by specific objectives (Thomas, R David, 2003). The result of this study reveals that teachers do have different perspectives according to what they experience themselves. While the characteristics according to several teachers who have been interviewed researchers are students who are active in the language learning process, students who realize that learning language is not easy, students who find strategies to practice using language in the classroom and outside the classroom, students who have good self- image and self-confidence, students who want to make mistakes.